The technology of formation of would-be managers’ constructive interaction skills (Pedagogy of Higher and Secondary Education, 2012)
Hahina N. The technology of formation of would-be managers’ constructive interaction skills.The technology of formation of would-be managers’ skills of constructive interaction in a conflict situation is introduced in the article. The technology components are determined. The formation of constructive interactionskills is carried out in accordance with the followings stages: diagnostic-motivational, theoretical, training, reflection-correctional and creative.
Keywords: educational technology; formation of skills of constructive interaction in a conflict situation; would-be managers